Теоретичні аспекти лізингового фінансування суб’єктів аграрного бізнесу - Трусова, Наталя Вікторівна; Trusova, Natalia; Тулуш, Леонід Дмитрович; Tulush, Leonid; Дараган, Андрій Анатолійович; Daragan, Andrii (My University, 2025)
UA: У статті розглянуто теоретичні аспекти лізингового фінансування суб’єктів аграрного бізнесу. З позиції інвестиційно-кредитного підходу та регулювання лізингових відносин у сільському господарстві, визначено власне трактування сутності лізингу, як ефективного фінансового інструменту в інвестиційній діяльності суб’єктів агробізнесу, який в умовах обмежених фінансових ресурсів у правовому полі дозволяє використовувати певне рухоме та нерухоме майно на оплатно-тимчасовій основі. Виокремлено специфічні ознаки лізингового фінансування суб’єктів аграрного бізнесу, що адаптовані до системних змін в кредитному механізмі банківських установ із залученням до цього процесу лізингових компаній на засадах власності до об’єкту лізингу. Обґрунтовано взаємодію чинників лізингового фінансування, що мотивують до використання кредитних ресурсів з метою забезпечення потреб та інтересів суб’єктів аграрного бізнесу. /// EN: The article considers theoretical aspects of leasing financing of agrarian business entities. Leasing financing as a symbiosis of credit investment and property rental on the basis of leasing relations and alternative forms of servicing the needs of agrarian business entities in the banking services market. Scientific approaches to interpreting the essence of the concept of "leasing" are grouped. From the position of the investment-credit approach and regulation of leasing relations in agriculture, the actual interpretation of the essence of leasing is determined as the most effective financial instrument in the investment activities of agrarian business entities, which, in conditions of limited financial resources in the legal field, allows the use of certain movable and immovable property on a fee-for-service basis. It is proved that to reduce the level of financial risk, financial leasing from the lessor bank best meets the economic interests of agrarian business entities, since when using operational leasing, the financial risk increases. It is substantiated that financial leasing as a type of investment activity is aimed at finding and attracting free financial resources in long-term assets with their subsequent transfer for temporary use on a paid basis. The specific features and advantages of leasing financing of agricultural business entities are grouped. The specific features of leasing financing are related to its flexibility, adaptability to systemic changes in the leasing business, which is interconnected by the credit mechanism of banking institutions and the involvement of leasing companies in this process, as well as the acquisition of special property relations when choosing an investment object and its conditions. The development of leasing financing of agricultural business entities becomes a field of interaction of factors (interpenetration of economies of different countries and the spread of new progressive management methods on this basis, activation of digital technologies in leasing operations, adaptation to structural changes in the agricultural and industrial sectors), which motivate its development and form a financial and credit mechanism, which is a set of forms and methods of creating and effectively using financial and credit resources, based on a term basis in order to ensure the needs and interests of agricultural structures.
Theoretical aspects of leasing financing of agricultural business entities
Keywords: лізингове фінансування; фінансовий лізинг; лізингова угода; банківські установи; лізингові компанії; суб’єкти аграрного бізнесу; leasing financing; financial leasing; leasing agreement; banking institutions; leasing companies; agribusiness entities